THE EFFECTIVENESS OF METHODS FOR GREAT LESSONS - Jabborova Dilafruz Sharofovna; Turaqulova Dilafruz Qahhorovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Good lesson planning is essential to the process of teaching and learning. A teacher who is prepared is well on his/her way to a successful instructional experience. The article shows the development of interesting lessons takes a great deal of time and effort. As a new teacher, you must be committed to spending the necessary time in this endeavor.